ANALISIS PENGARUH KARAKTERISTIK PERUSAHAAN DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP AGRESIVITAS PAJAK PADA PERUSAHAAN TAMBANG - Natalia Ursula Dande (Ma Chung Press, 2018)
The purpose of this study is to determine the effect of corporate characteristics and Corporate Social Responsibility to corporate tax aggressiveness. The legitimacy theory is used in this research as the grand theory. To see how the company can implement the expectations and demands of the community in the implementation of its business, CSR is regarded as an addition to the company's information as well as the community's demands for the reciprocity of the company. Characteristics of companies used in this study is profitability, inventory intensity, capital intensity and leverage on tax aggressiveness. The research is conducted in mining sector companies listing on BEI in 2013-2015. The number of sample is 18 companies, with non-probability sampling method, with purposive sampling technique. The research used descriptive analysis technique and multiple linear regression analysis. The result of this research is that there is no significant relationship between dependent variable with independent variable.